Kemampuan Pemahaman Konsep Matematika Siswa Ditinjau dari Minat Belajar dan Gender - Rahmat Winata; Rizki Nurhana Friantini (AlphaMath : Journal of Mathematics Education, 2020)
This study aims to analyze the conceptual understanding ability’s students of class X IIS SMA 1 Jelimpo 2018/2019 academic year in term of learning interests and gander. This type of research is a qualitative research. The subject selection used purposive sampling. The data collection used test and interview methods. The validity of the data used triangulation method. The results of this study show that male and female students who have high learning interest have the ability to understand the concept that being able to explain, to apply the relationship between concepts and procedures, and provide examples and not examples, but they are unable to develop concepts. Male students who have medium learning interest are able to explain and give examples and not examples, but are less able to apply the relationship between concepts and procedures and also unable to develop concepts. Female students who have medium learning interest are able to explain, to apply relationship between concepts and procedures, and to provide examples and not examples, but they are unable to explain and to develop concepts. Male students who have low learning interest are able to apply the relationship between concepts and procedures and to provide examples and not examples, but they are unable to explain and to develop concepts. Female students who have a low interest learning are unable to explain, unable to apply the relationship between concepts and procedures, unable to provide examples and not examples, and unable to develop concepts that have been learned.